Development and Evaluation of Drug Loaded Regenerated Bacterial Cellulose-Based Matrices as a Potential Dosage Form - Badshah, Munair; Ullah, Hanif; He, Feng; Wahid, Fazli; Farooq, Umar; Andersson, Mattias; Khan, Taous (Frontiers in Bioengineering and Biotechnology, 2020)
Bacterial cellulose (BC) is a highly pure form of cellulose and possesses superior physico-mechanical properties with wide range of applications. These properties of BC can further be improved by various modifications, including its regeneration from the BC solution. In the current research work, regenerated BC (R-BC) matrices were prepared using N-methyl-morpholine-oxide (NMMO; 50% w/w solution in water) and loaded with model drugs, i.e., famotidine or tizanidine. The characterization of drug loaded regenerated BC (R-BC-drug) matrices was carried out using Fourier transform infrared spectroscopy (FTIR), x-ray diffraction (XRD) analysis, scanning electron microscopy (SEM) and thermogravimetric analysis (TGA), which revealed the stability of matrices and successful drug loading. Results of dissolution studies showed immediate (i.e., > 90%) drug release in 30 min. The drugs release data was found to best fit into first order kinetics model having R2 values greater than 0.99 for all the formulations. These results indicated that regenerated BC-based matrices had the ability to be used for delivery of orally administered drugs.